1998
DOI: 10.1111/j.1651-2227.1998.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of Ureaplasma urealyticum colonization in preterm infants

Abstract: A cohort of 78 infants of gestational age less than 34 weeks was examined for Ureaplasma urealyticum colonization and neonatal morbidity. Ureaplasma urealyticum was cultured from nasopharyngeal, endotracheal and blood‐culture samples. A child was considered as being colonized if any sample was positive. The children with perinatal U. urealyticum colonization (n= 11; 14%) differed from those with no colonization (n= 67) in two important aspects: (i) they had higher leucocyte counts on the first (18.6 vs 12.4 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Some authors suggest that colonization with U. urealyticum and U. parvum in high density is associated with non-specific cervicitis (12) , whereas others suggest that there is not enough evidence to suggest that these bacteria cause cervicitis or PID (13) . However, several studies in pregnant women showed that the presence of these bacteria in amniotic-fluid or membranes might be associated with preterm labor, preterm premature rupture of membranes (PPROM), and neonatal infections (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Abele-Horn et al (21) showed that U. urealyticum was associated with preterm labor.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that colonization with U. urealyticum and U. parvum in high density is associated with non-specific cervicitis (12) , whereas others suggest that there is not enough evidence to suggest that these bacteria cause cervicitis or PID (13) . However, several studies in pregnant women showed that the presence of these bacteria in amniotic-fluid or membranes might be associated with preterm labor, preterm premature rupture of membranes (PPROM), and neonatal infections (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Abele-Horn et al (21) showed that U. urealyticum was associated with preterm labor.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly found in healthy persons, therefore, their pathogenic role can be difficult to prove in a small population of individuals. Meanwhile, several studies have reported that Ureaplasma are associated with some diseases including non-gonococcal urethritis, pregnancy complications and prenatal infections, more often than are normal flora [18-20]. Thus, it might be that Ureaplasma perturb homeostasis in the genital tract, which provides a survival advantage for C. trachomatis .…”
Section: Introductionmentioning
confidence: 99%
“…Ureaplasma species can be classified into two major groups: U. parvum (serovars 1, 3, 6, and 14) and U. urealyticum (serovars 2, 4, 5, and 7 to 13) (4, 5). U. parvum has been implicated in the morbidity and mortality of newborns (68). U. parvum serovar 3 is the most prevalent serovar detected in reproductive humans (9, 10).…”
Section: Genome Announcementmentioning
confidence: 99%